New Trends in Mechanism and Machine Science From Fundamentals to Industrial Applications - Flores, Paulo; Viadero, Fernando (Mechanisms and Machine Science, 2015)
This work presents the most recent research in the mechanism and machine science field and its applications. The topics covered include: theoretical kinematics, computational kinematics, mechanism design, experimental mechanics, mechanics of robots, dynamics of machinery, dynamics of multi-body systems, control issues of mechanical systems, mechanisms for biomechanics, novel designs, mechanical transmissions, linkages and manipulators, micro-mechanisms, teaching methods, history of mechanism science and industrial and non-industrial applications. This volume consists of the Proceedings of the 5th European Conference on Mechanisms Science (EUCOMES), that was held in Guimarães, Portugal, from September 16 - 20, 2014. The EUCOMES is the main forum for the European community working in Mechanisms and Machine Science.